Low-boron refining slag and preparation method thereof
By using calcium oxide, fluorite powder, high alumina bauxite, cerium oxide and magnesium carbonate in the refining slag, low melting point and low viscosity refined slag are prepared, which solves the problems of high melting point, poor fluidity and high smelting energy consumption in the prior art, and achieves efficient removal of boron content and inclusions in the steel, and improves the performance of the steel.
Patent Information
- Application Number
- CN202411703088.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the refined slag has a high melting point, poor fluidity and high smelting energy consumption, making it difficult to effectively remove boron content and inclusions in steel, affecting the performance of the steel.
The preparation method of low-boron refining slag is adopted to prepare refined slag with low melting point and low viscosity by synergistic use of raw materials such as calcium oxide, fluorite powder, high alumina bauxite, cerium oxide and magnesium carbonate to improve its fluidity and adsorption ability to inclusions.
The low melting point and low viscosity of the refined slag are achieved, the fluidity and the removal efficiency of boron and inclusions are improved, the energy consumption of smelting is reduced, and the purity of molten steel and the performance of steel are improved.
Smart Images

Figure BDA0005153851890000091 
Figure BDA0005153851890000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgy, and in particular to a low-boron refined slag and a preparation method thereof. Background Art
[0002] In recent years, with the development of the steel industry and the improvement of scientific research level, the market demand for high-quality steel has increased, and special requirements have been put forward for the performance of high-quality steel. Previous studies have shown that the optimization of refined slag composition is an effective way to control and produce high-clean steel. The composition and basicity of refined slag are important factors affecting the desulfurization and deoxidation depth of molten steel. At the same time, refined slag with excellent performance can also play an important role in protecting the inner lining of the furnace and absorbing non-metallic inclusions in steel, and has a certain control effect on the type, size, morphology and distribution of inclusions.
[0003] In the production of steel, non-metallic inclusions, especially boron compounds, will seriously affect the properties of steel, such as low-temperature impact toughness, yield strength, tensile strength, hardness and plasticity, etc. Therefore, by using refined slag with low boron content, these adverse effects can be reduced, thereby improving the properties of steel.
[0004] CN101956045A discloses a refining slag and a method for refining molten steel. The refining slag provided by the invention contains the following components by weight: 40-55 parts of CaO, 30-45 parts of SiO2, 10-25 parts of CaF2, ≤3 parts of Al2O3, ≤2 parts of TiO2, wherein the contents of Al2O3 and TiO2 are not 0, and the basicity CaO / SiO2 value of the refining slag is preferably 1.0-1.4. The purpose of the invention is to reduce the impurity content in molten steel such as cord steel and improve the cleanliness of the molten steel. However, due to the unsatisfactory fluidity of the refining slag and the low content of Al2O3, the apparent viscosity and melting point of the slag are both high, and the comprehensive performance is poor.
[0005] CN1718765A discloses a composite refining slag for converter steel refining and its adding method. The composite refining slag provided by the invention comprises the following chemical components by weight percentage: CaC2: 30-50%, Al2O3: 20-36%, SiO2: 8-18%, CaF2: 8-18%. The composite refining slag has a low melting point and can reduce the FeO in the ladle slag to below 1.0%, and the T[O] in the finished steel to 15×10 -6 Below, the S content drops to below 0.006%. However, the smelting energy consumption is high. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, the present invention provides a low-boron refined slag and a preparation method thereof. The refined slag provided by the present invention has the advantages of low melting point, good fluidity, good adsorption of steel inclusions and boron content, and reduced smelting energy consumption.
[0007] To achieve the above-mentioned purpose, the present invention provides a low-boron refining slag, wherein the chemical components of the low-boron refining slag include, by weight percentage: CaO: 45-60%, CaF2: 10-15%, Al2O3: 5-15%, SiO2: 2-5%, MgO: 5-9%, Ce2O3: 3-12%, and the rest are inevitable impurities.
[0008] Preferably, the chemical composition of the low-boron refined slag includes: CaO: 50-58%, CaF2: 11-13%, Al2O3: 6-10%, SiO2: 3-4%, MgO: 6-8%, Ce2O34-9%, and the rest are inevitable impurities.
[0009] Preferably, the low-boron refined slag is prepared by mixing the following raw materials, and the raw materials and their weight ratios are: 45-65 parts of calcium oxide, 11-16 parts of fluorite powder, 2-10 parts of flux, 1-3 parts of silicon dioxide, and 4-12 parts of accelerator.
[0010] Preferably, the calcium oxide content in the calcium oxide is ≥ 95% by weight.
[0011] Preferably, the calcium fluoride content in the fluorite powder is ≥85% by weight.
[0012] Preferably, the flux is selected from at least one of high-alumina bauxite, AD powder and aluminum ash.
[0013] Further preferably, the flux is high-alumina bauxite.
[0014] Preferably, the additive is selected from at least one or two of cerium oxide and magnesium additives.
[0015] Further preferably, the additive is formed by mixing cerium oxide and magnesium additive in a mass ratio of 10:(2-6).
[0016] Further preferably, the magnesium additive is selected from at least one of magnesium carbonate and magnesia powder.
[0017] Further preferably, the magnesium additive is magnesium carbonate.
[0018] The present invention also provides a method for preparing the above-mentioned low-boron refined slag, comprising the following steps:
[0019] Weigh calcium oxide, fluorite powder, flux, silicon dioxide and accelerator according to the formula ratio;
[0020] Mixing in a blender;
[0021] Melting furnace smelting;
[0022] Cooling and solidification;
[0023] broken;
[0024] Sieve.
[0025] Preferably, the method for preparing the low-boron refined slag comprises the following steps:
[0026] (1) Raw material inspection: Analyze the data strictly according to the raw material inspection method, and the quality inspection department makes judgments based on the standards;
[0027] (2) Warehouse entry: According to the judgment of the Quality Inspection Department, the warehouse shall mark the origin, quantity, date, specifications, etc., stack them neatly and in a standardized manner and register them in the warehouse account;
[0028] (3) Material collection: Calcium oxide, fluorite powder, flux, silicon dioxide and accelerator are weighed according to the formula ratio, and the materials used are strictly checked to see if they meet the formula requirements according to the formula notice issued by the technical department. The warehouse keeper identifies the materials, the batcher identifies the materials, and the batcher unpacks and inspects the materials. Raw materials that do not meet the formula requirements are rejected during the production process;
[0029] (4) Material feeding: various raw materials collected in step (3) are placed in the designated silo according to the current production technical standards. They must not be mixed or contaminated. Before feeding, ensure that the site is clean, identify the materials, distinguish the material names, specifications and models, and put them into the silo;
[0030] (5) Ingredients: Follow the technical formula requirements and operate accurately to ensure correct operation;
[0031] (6) Mixing with a mixer: strictly control the order of adding materials and mixing time;
[0032] (7) Melting in the melting furnace: Maintain uniform material feeding, control the temperature of the melting furnace, and ensure that all input materials are melted;
[0033] (8) Plate cooler: cooling and solidification;
[0034] (9) Crushing: crushing according to the operation requirements;
[0035] (10) Screening: Ensure the screen is intact, ensure the quality, and meet the screening standards;
[0036] (11) Packaging: Check the printing quality of the packaging products and whether the specifications, models, names, colors and other labels are complete. Stir once to make them evenly before packaging. Pack first and clean later. Sprinkle the cleaned products on the unpacked products. The measurement is accurate, the tying is standardized, the outer packaging is clean and tidy, and the labels are clear and complete.
[0037] (12) Warehousing: Handle with care, stack neatly and in a standardized manner, and store different products separately;
[0038] (13) Transportation: Three-layer waterproofing measures.
[0039] Preferably, in step (7), the temperature of the smelting furnace is controlled at 1400-1700°C.
[0040] Preferably, the crushing particle size in step (9) is controlled at 5-50 mm.
[0041] The calcium oxide in the present invention contains a high content of CaO, which is the main substance for improving the alkalinity of the slag, provides a higher alkalinity for the refined slag, and can promote it to form an insoluble compound with boron more effectively during the molten steel refining process, thereby removing it from the molten steel and reducing the boron content of the steel. At the same time, after the addition of CaO, the melting point and viscosity of the refined slag are less affected, and it has a higher desulfurization efficiency, and at the same time helps to improve the slag's adsorption capacity for inclusions.
[0042] The main component of the high-alumina bauxite in the present invention is Al2O3, which can be decomposed into Al2O3 with multiple pore structures, large specific surface area and high activity by heating. This high-activity Al2O3 can combine with CaO to form a variety of low-melting point compounds. These compounds have low melting points and help improve the fluidity of slag and desulfurization effect. In addition, the high-alumina bauxite can also produce a synergistic effect with cerium oxide. The Al2O3 in the high-alumina bauxite combines with cerium oxide to form low-melting point compounds, which helps the refined slag to melt at a lower temperature and have a lower viscosity, further reducing the overall melting point and viscosity of the slag, improving the fluidity of the slag, and improving the removal efficiency of the boron content and inclusions in the refined slag, thereby improving the purity of the molten steel.
[0043] In the present invention, magnesium carbonate can be decomposed to produce CO2 and MgO during the slag refining process. The MgO content in the slag of the present invention is maintained at 6-8%, which is beneficial to reducing the erosion of the slag on the steel, reducing the activity of SiO2, and helping to ensure the good fluidity of the slag and improve the purity of molten steel. In the present invention, magnesium carbonate and cerium oxide are used in coordination, and the two can produce a synergistic effect under high-temperature melting conditions to form a more effective fluxing substance, reduce the melting point and viscosity, and help improve the melting and flow characteristics of the slag, and at the same time help to improve the removal efficiency of the slag for boron and inclusions, and improve the quality of steel.
[0044] The addition of fluorite powder in the present invention further increases the basicity of the slag. At the same time, the introduced fluorine ions break the network structure of the slag, play a fluxing role, help to reduce the melting point of the slag, improve the fluidity of the slag, ensure that the refined slag can be melted evenly and quickly on the surface of molten steel and has excellent fluidity, and further ensure that the refined slag has good inclusion adsorption and boron removal capabilities.
[0045] Silicon dioxide is one of the basic components of the refined slag in the present invention, and has an important influence on the melting point of the refined slag. In the refined slag system of the present invention, SiO2 maintains a relatively low activity, which helps to ensure good fluidity of the refined slag.
[0046] The cerium oxide in the present invention has high catalytic activity and strong reducibility, which may help to reduce the oxidation state of boron and effectively promote the removal of boron and inclusions in steel; at the same time, cerium oxide and magnesium carbonate may produce a synergistic effect under high-temperature melting conditions to form a more effective fluxing substance, reduce the melting point and viscosity, and can combine with Al2O3 in high-alumina bauxite to form a low-melting point compound, which helps the refined slag to melt at a lower temperature and have a lower viscosity, which can effectively improve the melting and flow characteristics of the slag, and at the same time help to improve the slag to improve the removal efficiency of boron and inclusions, and improve the quality of steel.
[0047] AD powder in the present invention is a commonly used steelmaking accelerator, which has the functions of deoxidation, slag washing, promoting desulfurization, and preparing refined slag. Introducing AD powder in the process of preparing refined slag helps to improve the oxidizability of slag and improve the fluidity of slag, and promotes the removal of steel impurities and boron by refined slag. However, AD powder has a high cost, so high-alumina bauxite with lower cost and better effect is preferably selected as flux in the formula of the present invention.
[0048] Beneficial effects of the present invention:
[0049] Compared with the prior art, the present invention improves the ingredients and makes reasonable proportions, mixes magnesium carbonate and cerium oxide as promoters, and introduces the promoter into the refined slag, and uses it in conjunction with calcium oxide, fluorite powder, high-alumina bauxite and silicon dioxide. Through multi-faceted mutual coordination and restriction among the ingredients, the prepared refined slag has a lower melting point and viscosity and better fluidity, thereby solving the technical problems of high melting point of refined slag, poor slag fluidity and high smelting energy consumption in the preparation method of steel refined slag system in the prior art. In addition, the refined slag provided by the present invention has good inclusion adsorption and boron removal ability, can effectively reduce the boron content and inclusions in steel, is beneficial to improving the purity of molten steel and reducing smelting energy consumption. DETAILED DESCRIPTION
[0050] Parameters for specific chemical substances used, sources.
[0051] Calcium oxide, particle size: 325 mesh, CaO content: 95%;
[0052] Fluorite powder, specification: 200mm, CaF2 content: 90%;
[0053] High alumina, specification: 3mm, Al2O3 content: 85%;
[0054] AD powder, particle size: 100 mesh, Al content: 18%, Al2O3 content: 65%, SiO2 content ≤10%;
[0055] Aluminum ash, specification: 3mm, Al content: 20%, Al2O3 content: 50%;
[0056] Magnesia powder, particle size: 325 mesh, MgO content: 98%;
[0057] Silicon dioxide, particle size: 100 mesh, purity: 99%;
[0058] Cryolite powder, particle size: 325 mesh, active ingredient content: 99%;
[0059] Aluminum particles, specification: 1mm, Al content: 99%.
[0060] Example 1
[0061] A method for preparing low-boron refined slag comprises the following steps:
[0062] (1) Raw material inspection: Analyze the data strictly according to the raw material inspection method, and the quality inspection department makes judgments based on the standards;
[0063] (2) Warehouse entry: According to the judgment of the Quality Inspection Department, the warehouse shall mark the origin, quantity, date, specifications, etc., stack them neatly and in a standardized manner and register them in the warehouse account;
[0064] (3) Material collection: Weigh 50 parts by weight of calcium oxide, 13 parts by weight of fluorite powder, 8 parts by weight of high-alumina bauxite, 2.5 parts by weight of silicon dioxide, and 10 parts by weight of accelerator according to the formula ratio, and strictly check whether the materials used meet the formula requirements according to the formula notice issued by the technical department. The warehouse keeper identifies the materials, the batcher identifies the materials, and the batcher unpacks and inspects the materials. Raw materials that do not meet the formula requirements will be rejected during the production process;
[0065] (4) Material feeding: various raw materials collected in step (3) are placed in the designated silo according to the current production technical standards. They must not be mixed or contaminated. Before feeding, ensure that the site is clean, identify the materials, distinguish the material names, specifications and models, and put them into the silo;
[0066] (5) Ingredients: Follow the technical formula requirements and operate accurately to ensure correct operation;
[0067] (6) Mixing with a mixer: strictly control the order of adding materials and mixing time;
[0068] (7) Melting in the melting furnace: Keep the material evenly fed, the temperature of the melting furnace is 1600℃, and ensure that all the input materials are melted;
[0069] (8) Plate cooler: cooling and solidification;
[0070] (9) Crushing: Crushing is carried out according to the operation requirements, and the product crushing particle size is 30±5mm;
[0071] (10) Screening: Ensure the screen is intact, ensure the quality, and meet the screening standards;
[0072] (11) Packaging: Check the printing quality of the packaging products and whether the specifications, models, names, colors and other labels are complete. Stir once to make them evenly before packaging. Pack first and clean later. Sprinkle the cleaned products on the unpacked products. The measurement is accurate, the tying is standardized, the outer packaging is clean and tidy, and the labels are clear and complete.
[0073] (12) Warehousing: Handle with care, stack neatly and in a standardized manner, and store different products separately;
[0074] (13) Transportation: three layers of waterproofing measures;
[0075] The promoter in step (3) is a mixture of cerium oxide and magnesium carbonate in a mass ratio of 10:4.
[0076] Example 2
[0077] A method for preparing low-boron refined slag, which is different from that of Example 1 in that the promoter in step (3) is magnesium carbonate;
[0078] That is, the raw material formula is: 50 parts by weight of calcium oxide, 13 parts by weight of fluorite powder, 8 parts by weight of high-alumina bauxite, 2.5 parts by weight of silicon dioxide, and 10 parts by weight of magnesium carbonate.
[0079] Example 3
[0080] A method for preparing low-boron refined slag, which differs from Example 1 in that the promoter in step (3) is cerium oxide;
[0081] That is, the raw material formula is: 50 parts by weight of calcium oxide, 13 parts by weight of fluorite powder, 8 parts by weight of high-alumina bauxite, 2.5 parts by weight of silicon dioxide, and 10 parts by weight of cerium oxide.
[0082] Example 4
[0083] A method for preparing low-boron refined slag, which differs from Example 1 in that the accelerator in step (3) is a mixture of cerium oxide and magnesia powder in a mass ratio of 10:4.
[0084] Example 5
[0085] A method for preparing low-boron refined slag, which differs from Example 1 in that 8 parts by weight of high-alumina bauxite in its raw material formula is replaced by 8 parts by weight of aluminum ash;
[0086] That is, the raw material formula is: 50 parts by weight of calcium oxide, 13 parts by weight of fluorite powder, 8 parts by weight of aluminum ash, 2.5 parts by weight of silicon dioxide, and 10 parts by weight of accelerator;
[0087] The promoter is a mixture of cerium oxide and magnesium carbonate in a mass ratio of 10:4.
[0088] Example 6
[0089] A method for preparing low-boron refined slag, which differs from Example 1 in that 8 parts by weight of high-alumina bauxite in its raw material formula is replaced by 8 parts by weight of AD powder;
[0090] That is, the raw material formula is: 50 parts by weight of calcium oxide, 13 parts by weight of fluorite powder, 8 parts by weight of AD powder, 2.5 parts by weight of silicon dioxide, and 10 parts by weight of accelerator;
[0091] The promoter is a mixture of cerium oxide and magnesium carbonate in a mass ratio of 10:4.
[0092] Comparative Example 1
[0093] A method for preparing low-boron refined slag, which differs from Example 1 in that high-alumina bauxite is not added to the raw material formula;
[0094] That is, the raw material formula is: 50 parts by weight of calcium oxide, 13 parts by weight of fluorite powder, 2.5 parts by weight of silicon dioxide, and 10 parts by weight of accelerator;
[0095] The promoter is a mixture of cerium oxide and magnesium carbonate in a mass ratio of 10:4.
[0096] Comparative Example 2
[0097] A method for preparing low-boron refined slag, which differs from Example 1 in that no accelerant is added to the raw material formula;
[0098] That is, the raw material formula is: 50 parts by weight of calcium oxide, 13 parts by weight of fluorite powder, 8 parts by weight of high-alumina bauxite, and 2.5 parts by weight of silicon dioxide.
[0099] Comparative Example 3
[0100] A method for preparing low-boron refined slag, which differs from Example 1 in that fluorite powder is not added to the raw material formula;
[0101] That is, the raw material formula is: 50 parts by weight of calcium oxide, 8 parts by weight of high-alumina bauxite, 2.5 parts by weight of silicon dioxide, and 10 parts by weight of accelerator;
[0102] The promoter is a mixture of cerium oxide and magnesium carbonate in a mass ratio of 10:4.
[0103] Comparative Example 4
[0104] A method for preparing low-boron refined slag, which differs from Example 1 in that 13 parts by weight of fluorite powder in the raw material formula is replaced with 13 parts by weight of cryolite powder;
[0105] That is, the raw material formula is: 50 parts by weight of calcium oxide, 13 parts by weight of cryolite powder, 8 parts by weight of high-alumina bauxite, 2.5 parts by weight of silicon dioxide, and 10 parts by weight of accelerator;
[0106] The promoter is a mixture of cerium oxide and magnesium carbonate in a mass ratio of 10:4.
[0107] Comparative Example 5
[0108] A method for preparing low-boron refined slag, which differs from Example 1 in that 8 parts by weight of high-alumina bauxite in its raw material formula is replaced with 8 parts by weight of aluminum particles;
[0109] That is, the raw material formula is: 50 parts by weight of calcium oxide, 13 parts by weight of fluorite powder, 8 parts by weight of aluminum particles, 2.5 parts by weight of silicon dioxide, and 10 parts by weight of accelerator;
[0110] The promoter is a mixture of cerium oxide and magnesium carbonate in a mass ratio of 10:4.
[0111] Comparative Example 6
[0112] A method for preparing low-boron refined slag, which differs from Example 1 in that the promoter in step (3) is a mixture of lanthanum oxide and magnesium carbonate in a mass ratio of 10:4.
[0113] Test Example 1
[0114] The composition of the refined slag prepared in Example 1 was measured, and the measurement results are shown in Table 1;
[0115] The physical properties of the refined slags prepared in Examples 1-6 and Comparative Examples 1-6 were tested using a slag melting temperature characteristic tester and a slag viscosity tester. The measurement results are shown in Table 2.
[0116] Table 1 Composition of refined slag of Example 1 (wt%)
[0117]
[0118] Table 2 Melting point and viscosity test results of refined slag
[0119] Melting point(℃) Viscosity at 1500℃(Pa·s) Example 1 1412 0.31 Example 2 1456 0.38 Example 3 1442 0.36 Example 4 1435 0.34 Example 5 1437 0.35 Example 6 1413 0.30 Comparative Example 1 1487 0.45 Comparative Example 2 1472 0.42 Comparative Example 3 1499 0.48 Comparative Example 4 1476 0.41 Comparative Example 5 1463 0.39 Comparative Example 6 1475 0.41
[0120] Refining slag with low melting point helps to form slag quickly, which can speed up the refining process of molten steel, reduce smelting time, save production costs, and slag with low melting point is easier to mix with molten steel, which helps to remove impurities. Refining slag with low viscosity has good fluidity, which can better contact with molten steel, increase mass transfer effect, and is conducive to the floating and adsorption of inclusions. Slag with good fluidity can more easily adsorb impurities in steel and remove them from molten steel. Therefore, lowering the melting point and viscosity of refining slag helps to improve the removal efficiency of refining slag for inclusions, thereby improving the purity of molten steel.
[0121] It can be seen from Table 2 that by comparing Examples 1-6 and Comparative Examples 1-6, it is found that the melting point and viscosity of Examples 1-6 are significantly lower than those of Comparative Examples 1-6, among which the melting point and viscosity of Example 1 are the lowest, indicating that the refined slag prepared in the embodiment of the present invention has a lower melting point and viscosity and better fluidity.
[0122] By comparing Example 1, Examples 2-3 and Comparative Example 2, it is found that in Comparative Example 2, no promoter is added, the melting point is increased to 1472°C, and the viscosity at 1500°C is 0.42 Pa·s, which indicates that the absence of promoter will lead to an increase in melting point and viscosity; in Example 2, magnesium carbonate is used as a promoter, and in Example 3, cerium oxide is used as a promoter, and the melting point and viscosity are increased compared with Example 1, indicating that the fluxing effect of using magnesium carbonate or cerium oxide alone is not as good as the mixture of cerium oxide and magnesium carbonate. The reason for this may be that the mixture of cerium oxide and magnesium carbonate has a synergistic effect. The two substances undergo a specific chemical reaction during the melting process to form a low-melting compound, which enables the mixture of the two to form a more active interface in the molten system, thereby reducing the melting point and viscosity.
[0123] By comparing Example 1, Example 4 and Comparative Example 6, it is found that in Example 4, a mixture of cerium oxide and magnesia powder is used as a promoter, with a melting point of 1435°C and a viscosity of 0.34 Pa·s, and the effect is not as good as that in Example 1; the promoter in Comparative Example 6 is a mixture of lanthanum oxide and magnesium carbonate, with a melting point of 1475°C and a viscosity of 0.41 Pa·s at 1500°C, and the effect is not as good as that in Example 1; it shows that the effects of using a mixture of cerium oxide and magnesia powder as a promoter and using a mixture of lanthanum oxide and magnesia powder as a promoter are not as good as the mixture of cerium oxide and magnesium carbonate. The reason for this may be that the carbon dioxide gas produced by the decomposition of magnesium carbonate at high temperature may help to break the network structure of the slag and help to promote the melting and flow of the slag, while magnesia powder, as magnesium oxide that has been calcined and formed, may not have this gas release effect. In addition, its reaction activity may be lower than that of magnesium carbonate, and its interaction with cerium oxide in the high-temperature molten state is not as good as that of magnesium carbonate, so it is not as effective as magnesium carbonate in reducing the melting point and viscosity. Compared with lanthanum oxide, Ce in cerium oxide 4+ The ionic radius is smaller than that of La in lanthanum oxide. 3+ions, which may make Ce 4+ Ions can more easily replace other cations in the slag, thereby more effectively destroying the slag network structure and reducing the melting point and viscosity of the slag.
[0124] By comparing Example 1, Examples 5-6, Comparative Example 1 and Comparative Example 5, it is found that in Comparative Example 1, no high alumina is added, the melting point is increased to 1487°C, and the viscosity at 1500°C is 0.45 Pa·s. The melting point and viscosity change significantly compared with Example 1, which shows that the addition of high alumina helps to reduce the melting point and viscosity of the refined slag; in Example 5, high alumina is replaced by aluminum ash, and the melting point and viscosity change greatly compared with Example 1; in Example 6, high alumina is replaced by AD powder, and the melting point and viscosity do not change significantly compared with Example 1; in Comparative Example 5, high alumina is replaced by aluminum particles, with a melting point of 1463°C and a viscosity of 0.39 Pa·s at 1500°C, which is not as good as Example 1; it shows that AD powder, aluminum ash, and aluminum particles are used as substitutes for high alumina, and AD powder has similar effects to high alumina, while aluminum ash and aluminum particles are not as effective as high alumina. However, due to the high cost of AD powder, the present invention selects high alumina with lower cost and better effect. The reason may be that high-alumina bauxite contains a high level of aluminum oxide (Al2O3). Adding high-alumina bauxite to refined slag can increase the Al2O3 content of the slag, thereby helping to reduce the melting point and viscosity of the slag. Al2O3, as an acidic oxide, can combine with CaO to form a variety of low-melting point compounds. These compounds have a low melting point and help improve the fluidity of the slag. Compared with high-alumina bauxite, the chemical composition of aluminum ash is complex. Although the main component is aluminum oxide, it contains more impurities and harmful ions. These impurities may affect its performance in refined slag and reduce its fluxing effect. Compared with high-alumina bauxite, the physical form and reactivity of aluminum particles are different from those of high-alumina bauxite. Aluminum particles may need to undergo a melting and dissolution process in the slag before they can react with other components in the slag. This process may not be as efficient as high-alumina bauxite directly participating in the formation of low-melting point compounds.
[0125] Comparing Example 1 with Comparative Examples 3-4, it is found that in Comparative Example 3, no fluorite powder is added, and the melting point is increased to 1499°C, and the viscosity at 1500°C is 0.48Pa·s, which shows that the addition of fluorite powder helps to reduce the melting point and viscosity; in Comparative Example 4, the fluorite powder is replaced by cryolite powder, and the melting point is 1476°C, and the viscosity at 1500°C is 0.41Pa·s, which is not as good as in Example 1, indicating that cryolite powder is not effective as a substitute for fluorite powder. Analysis shows that the reason may be that the fluorite powder contains halogen elements F, which can react with oxides in the slag such as aluminum oxide (Al2O3) and calcium oxide (CaO) to generate low-melting-point compounds, thereby reducing the melting point of the entire slag. At the same time, the fluoride ions (F-) in the fluorite powder can destroy the oxide network structure in the slag, reduce the polymerization degree of oxygen ions in the network, thereby reducing the viscosity of the slag and improving its fluidity. Compared with fluorite powder, cryolite powder has a relatively high melting point and a different chemical structure from fluorite powder. It may not form a low-melting-point phase with good fluidity in the slag like fluorite powder.
[0126] In summary, the present invention adopts fluorite powder, high-alumina bauxite and calcium oxide to reduce the melting point of refined slag and improve its fluidity. At the same time, the introduction of cerium oxide and magnesium carbonate as promoters can help further reduce the melting point and viscosity of refined slag and improve its fluidity.
[0127] Test Example 2
[0128] Steels were prepared using the refined slags prepared in Examples 1-6 of the present invention and Comparative Examples 1-6, respectively. The preparation of the steels included conventional smelting process steps, namely converter smelting, LF refining, continuous casting and hot rolling, wherein the refined slag was used in the LF refining step; the prepared steels were recorded as Example 1-6 and Comparative Example 1-6, respectively; the boron content in each group of steels was tested, and the test results are shown in Table 3 below; the 500 mm diameter of the steels was analyzed by scanning electron microscopy. 2 The number distribution of inclusions larger than 5 μm and the maximum size of inclusions in the area are shown in Table 3.
[0129] Table 3
[0130]
[0131] As shown in Table 3, by comparing Examples 1-6 with Comparative Examples 1-6, it is found that the boron content in the steel of Examples 1-6 is lower than that of Comparative Examples 1-6, and the number density and maximum size of inclusions are lower than those of Comparative Examples 1-6. Among them, Example 1 has the lowest boron content (0.0002wt%) and the least number of inclusions (0.13 / mm 2 ), and the maximum size is the smallest (12 μm), indicating that the refined slag prepared in the embodiment of the present invention has a good effect of reducing the boron content in steel and adsorbing inclusions.
[0132] Comparing Example 1, Example 2-3 and Comparative Example 2, it is found that in Comparative Example 2, no promoter is added, the boron content is significantly increased (0.0027wt%), and the number of inclusions is increased (0.46 / mm 2 ), the maximum size increases (33μm), which indicates that the lack of promoter will lead to an increase in boron content and aggravate the inclusion problem; magnesium carbonate is used as a promoter in Example 2, and cerium oxide is used as a promoter in Example 3. The boron content, inclusion number density and maximum size increase compared with Example 1, indicating that the effect of using magnesium carbonate or cerium oxide alone in reducing the boron content and the number and size of inclusions is not as good as the mixture of cerium oxide and magnesium carbonate. The reason for this may be that cerium oxide has high catalytic activity and strong reducibility, which may help to reduce the oxidation state of boron and effectively promote the removal of boron and inclusions in steel. At the same time, cerium oxide and magnesium carbonate produce synergistic effects under high-temperature melting conditions to form more effective fluxing substances, reduce melting points and viscosity, and further improve the removal efficiency of boron and inclusions.
[0133] By comparing Example 1, Example 4 and Comparative Example 6, it is found that in Example 4, a mixture of cerium oxide and magnesia powder is used as a promoter, the boron content is increased (0.0007wt%), and the number of inclusions is increased (0.16 / mm 2 ), the maximum size increased (14 μm), the effect was not as good as Example 1; in Comparative Example 6, the promoter was a mixture of lanthanum oxide and magnesium carbonate, the boron content was significantly increased (0.0020 wt%), and the number of inclusions was significant (0.42 / mm 2 ), the maximum size is obvious (31μm), and the effect is not as good as Example 1; it shows that the effect of using a mixture of cerium oxide and magnesium sand powder as a promoter and a mixture of lanthanum oxide and magnesium sand powder as a promoter is not as good as the mixture of cerium oxide and magnesium carbonate. The reason for this may be that the interaction between magnesium sand powder and cerium oxide is not as good as that of magnesium carbonate, resulting in the failure of magnesium sand powder to effectively form a synergistic effect with cerium oxide, thereby affecting its promotion effect. Therefore, it is not as good as the mixture of cerium oxide and magnesium carbonate in reducing boron content and inclusion adsorption. Compared with cerium oxide, the mixture of lanthanum oxide and magnesium carbonate may not be as good as cerium oxide and magnesium carbonate in activity matching, and lanthanum oxide may not provide the same catalytic activity and reducibility as cerium oxide, thereby affecting its promotion effect.
[0134] By comparing Example 1, Examples 5-6, Comparative Example 1 and Comparative Example 5, it is found that in Comparative Example 1, no high-alumina bauxite is added, and the boron content (0.0013wt%) and the number of inclusions (0.23 pieces / mm2) are increased compared with Example 1, and the maximum size of inclusions (22μm) is also increased, which shows that the addition of high-alumina bauxite helps to reduce the boron content and inclusion problems; in Example 5, high-alumina bauxite is replaced by aluminum ash, and the boron content (0.0005wt%) and the number of inclusions (0.15 pieces / mm2) are increased. 2 ) is increased compared with Example 1, but the maximum size of inclusions (15μm) does not change much; in Example 6, high-alumina bauxite is replaced by AD powder, and the boron content (0.0003wt%) and the number of inclusions (0.13 / mm 2 ) is similar to Example 1, with the same maximum size inclusions (13 μm); in Comparative Example 5, high-alumina bauxite is replaced by aluminum particles, with a boron content (0.0015 wt%) and a number of inclusions (0.42 pcs / mm 2 ) is significantly increased compared with Example 1, and the maximum size of inclusions (30μm) changes greatly; it shows that when AD powder, aluminum ash, and aluminum particles are used as substitutes for high-alumina bauxite, AD powder and high-alumina bauxite have similar effects, while aluminum ash and aluminum particles are not as effective as high-alumina bauxite. However, due to the high cost of AD powder, the present invention selects high-alumina bauxite with lower cost and better effect. The reason for this analysis may be that Al2O3 in high-alumina bauxite combines with CaO in slag to form low-melting-point compounds, which helps to reduce the melting point and viscosity of the slag. At the same time, the addition of high-alumina bauxite can promote the combination of sulfide inclusions in steel with calcium aluminates in slag to form large inclusions that are easy to float, which may enhance the adsorption capacity of refined slag for boride inclusions in steel, which is beneficial to improve the removal efficiency of refined slag for boron content and inclusions, thereby improving the purity of molten steel.
[0135] Comparing Example 1 with Comparative Examples 3-4, it is found that in Comparative Example 3, no fluorite powder is added, the boron content (0.0024wt%) and the number of inclusions (0.38 / mm 2 ) is significantly increased compared with Example 1, and the maximum size of inclusions (26μm) is also increased, which shows that the addition of fluorite powder has a positive effect on reducing the boron content and inclusion problems; in Comparative Example 4, fluorite powder is replaced by cryolite powder, and the boron content (0.0018wt%) and the number of inclusions (0.35 / mm 2) is increased compared with Example 1, and the maximum size of inclusions (24μm) is also increased, which shows that cryolite powder is not effective as a substitute for fluorite powder. Analysis shows that the reason may be that fluorite powder is beneficial to reduce the viscosity of slag and improve its fluidity, thereby facilitating the slag's ability to adsorb and remove inclusions, resulting in a reduction in the boron content, number and size of inclusions in the steel. Compared with fluorite powder, it may be because the solubility and reactivity of cryolite powder in slag are not as good as those of fluorite powder, which may lead to the inability to effectively form a slag phase that is conducive to the removal of inclusions, thereby affecting the removal efficiency of boride inclusions, making the boron content reduction effect not as good as that of fluorite powder.
[0136] In summary, the synergistic use of fluorite powder, high-alumina bauxite and calcium oxide in the present invention is beneficial to reducing the boron content in steel, improving the adsorption effect on inclusions, improving the purity of molten steel, and reducing steelmaking costs. At the same time, the synergistic use of cerium oxide and magnesium carbonate as promoters is helpful to further reduce the boron content in steel and improve the adsorption effect on inclusions.
Claims
1. A low-boron refined slag, characterized in that: In terms of weight percentage, the chemical composition of the low-boron refined slag includes: CaO: 45-60%, CaF2: 10-15%, Al2O3: 5-15%, SiO2: 2-5%, MgO: 5-9%, Ce2O3: 3-12%, and the rest are inevitable impurities.
2. The low-boron refined slag according to claim 1, characterized in that: The chemical composition of the low-boron refined slag includes: CaO: 50-58%, CaF2: 11-13%, Al2O3: 6-10%, SiO2: 3-4%, MgO: 6-8%, Ce2O3 4-9%, and the rest are inevitable impurities.
3. The low-boron refined slag according to claim 1, characterized in that: The low-boron refined slag is prepared by mixing the following raw materials, and the raw materials and their weight ratios are: 45-65 parts of calcium oxide, 11-16 parts of fluorite powder, 2-10 parts of flux, 1-3 parts of silicon dioxide, and 4-12 parts of accelerator.
4. The low-boron refined slag according to claim 3, characterized in that: Calculated by weight percentage, the calcium oxide content in the calcium oxide is ≥95%; the calcium fluoride content in the fluorite powder is ≥85%.
5. The low-boron refined slag according to claim 3, characterized in that: The flux is selected from at least one of high-alumina bauxite, AD powder and aluminum ash.
6. The low-boron refined slag according to claim 3, characterized in that: The additive is selected from at least one or two of cerium oxide and magnesium additives; the additive is prepared by mixing cerium oxide and magnesium additives in a mass ratio of 10:(2-6).
7. The low-boron refined slag according to claim 6, characterized in that: The magnesium additive is selected from at least one of magnesium carbonate and magnesium sand powder.
8. The method for preparing low-boron refined slag according to any one of claims 3 to 7, characterized in that: The following steps are involved: Weigh calcium oxide, fluorite powder, flux, silicon dioxide and accelerator according to the formula ratio; Mixing in a blender; Melting furnace smelting; Cooling and solidification; broken; Sieve.
9. The method for preparing low-boron refined slag according to claim 8, characterized in that: The temperature of the smelting furnace is controlled at 1400-1700°C.
10. The method for preparing low-boron refined slag according to claim 8, characterized in that: The crushing particle size is controlled at 5-50 mm.
Citation Information
Patent Citations
Refining slag and method for refining molten steel
CN101956045A
Composite refining slag for converter molten steel refining and its adding method
CN1718765A
Cited By
High-silicon-aluminum coal of composite fluxing agent and preparation method of high-silicon-aluminum coal
CN121427587A